Peripheral Nerve Stimulation in the Treatment of Chronic Pain Syndromes From Nerve Injury: A Multicenter Observational Study. Issue 4 (16th November 2016) - Colini Baldeschi, Gianni; Dario, Alessandro; De Carolis, Giuliano; Luxardo, Nicola; Natale, Massimo; Nosella, Paola; Papa, Alfonso; Raggi, Massimiliano; Reverberi, Claudio
Abstract : Introduction: Assessing the feasibility, technical implications, and clinical benefits of peripheral nerve stimulation (PNS) performed by an implantable pulse generator (IPG) located close to the stimulation site. Materials and Methods: Selected patients were affected by neuropathic pain associated with a documented peripheral nerve lesion, refractory to conventional surgical or pharmacological treatment. A PNS system specifically designed for peripheral placement (Neurimpulse, Padova, Italy) was implanted and followed for six months, recording the degree of patient's satisfaction (PGI‐I questionnaire), the pain numerical rating scale (NRS) and the quality of life (SF36 questionnaire), as well as any change in drug regimen and work capability. The statistical significance of differences was determined by the paired Student's t ‐test. Results: A total of 58 patients were referred to permanent IPG implantation. Stimulation failure due to lead damage or dislocation was noticed in two cases (3.4%) in six months. At the follow‐up end, the relative NRS reduction averaged −58 ± 30% ( p  < 10 −6 ) and was greater than 50% in 69% of the cases. Quality‐of‐life physical and mental indices were increased by 18% ( p  < 0.005) and 29% ( p  < 0.0005), respectively. The administration of antalgic drugs was stopped in 55% and reduced in 16% of the patients. Low‐energy stimulation was possible in most cases, resulting in an IPG estimated life of 80 ± 35 months. Conclusions: Successful PNS was achieved with a stimulation system designed for peripheral location. This new technology reduced the incidence of lead‐related adverse events and the energy cost of the treatment.